Michigan's war the Civil War in documents - Quist, John W. 1960- (Civil War in the great interior, 2018)
"When it came to the Civil War, Michiganians never spoke with one voice. At the beginning of the conflict, family farms defined the southern Lower Peninsula, while a sparsely settled frontier characterized the state's north. Although differing strategies for economic development initially divided Michigan's settlers, by the 1850s Michiganians' attention increasingly focused on slavery, race, and the future of the national union. They exchanged charges of treason and political opportunism while wrestling with the meanings of secession, the national union, emancipation, citizenship, race, and their changing economy. Their actions launched transformations in their communities, their state, and their nation in ways that Americans still struggle to understand. Building upon the current scholarship of the Civil War, the Midwest, and Michigan's role in the national experience, Michigan's War is a documentary history of the Civil War era as told by the state's residents and observers in private letters, reminiscences, newspapers, and other contemporary sources. Clear annotations and thoughtful editing allow teachers and students to delve into the political, social, and military context of the war, making it ideal for classroom use"...